The preciseness of preschoolers: Differences by gender - Marković Živorad (University of Kragujevac - Faculty of Pedagogy, Užice, 2017)
The goal of this work was to study eventual differences in preciseness of the preschoolers. The research was realized in a preschool 'Decija Radost' in Svilajnac in the first term of 2017/2018 school year. 116 preschoolers participated in this research. They were divided into two sub samples according to gender: 62 boys and 54 girls. For the evaluation of the preciseness six standardized movement tasks were used: rolling of a ball under the chair, throwing of a loop onto the post, shooting of vertical targets, shooting of a vertical square, putting the ball into the basket and shooting of the clubs. Multivariant analysis of the variance was applied, discriminative analysis, Roy's test. The values of the multivariant analysis of the variance and discriminative analysis indicate that between boys and girls in relation to all six researched motor variables there is statistically significant difference and clearly defined imit with the level of statistical significance p = 0,000. The significant statistical difference was stated by the use of Roy's test between boys and girls in relation to all six studied variables and it is in favour of the boys.